From Emancipation through Employment to Emancipation through Entrepreneurship: An Analysis of the Special Labor Market Initiatives (BRYT) and Tax Deduction for Domestic Services (RUT) in Sweden - Kvist, Elin; Overud, Johanna (Nordic Journal of Working Life Studies, 2015)
Debates on gender equality policy in Sweden assume that women’s labor market participation is central to gender equality and should be promoted via special initiatives and programs. This paper examines how gender equality discourses have changed over time, analyzing Swedish state labor market policy in the 1980s and 1990s, special labor market initiatives to eliminate gender segregation and encourage nontraditional gendered work choices, and contemporary state subsidies for paid domestic work (i.e., tax deduction for domestic services). Critically interpreting these reforms reveals consistencies and continuities in how labor market participation is viewed as the key promoter of gender equality, revealing transformations in how gender equality is understood and constructed. A transition is discernible from state-funded programs and reforms to governmental agencies/authorities and state subsidies to promote enterprise and the growth of specific labor market sectors.